2022
DOI: 10.1007/s10549-022-06713-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of metastatic hormone receptor-positive, HER2-negative breast cancer (MBC) after CDK 4/6 inhibitors: a retrospective single-institution study

Abstract: Cyclin dependent kinase 4/6 inhibitors (CDK4/6is), in combination with endocrine therapy (ET), are standard either in the rst (1L) or second line (2L) setting for the treatment of hormone receptor (HR) positive, HER2-negative metastatic breast cancer (MBC). However, the optimal sequencing of treatments after progression on CDK4/6i remains unknown. We performed a single institution analysis to identify treatments and outcomes after progression on a CDK4/6i. MethodsWe identi ed patients with HR-positive, HER2-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…3 ). The weighted average median rwPFS for single-agent ET was 3.9 months ( n = 92 total patients) and was derived using data from two studies reporting median rwPFS values of 3.3 months ( n = 70) [ 38 ] and 6.0 months ( n = 22) [ 40 ]. For one study ( n = 7) that reported outcomes for single agent ET, median rwPFS was not reached during the follow-up period; as such, this study was excluded from the weighted average median rwPFS calculation [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 ). The weighted average median rwPFS for single-agent ET was 3.9 months ( n = 92 total patients) and was derived using data from two studies reporting median rwPFS values of 3.3 months ( n = 70) [ 38 ] and 6.0 months ( n = 22) [ 40 ]. For one study ( n = 7) that reported outcomes for single agent ET, median rwPFS was not reached during the follow-up period; as such, this study was excluded from the weighted average median rwPFS calculation [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Safety and tolerability data were reported in two studies [ 40 , 45 ]. One study investigating 2 L administration of the chemotherapy agent eribulin mesylate reported 27 patients (22.3%) with neutropenia, 3 patients (2.5%) with febrile neutropenia, 10 patients (8.3%) with peripheral neuropathy, and 14 patients (11.6%) with diarrhea [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of endocrine monotherapy as a comparator for second-/third-line treatment in ER1, HER2-aBC, while commonly used, might be argued in some regions where combination therapy is preferred, such as the United States (especially with fit patients). 6,32 Inherent to the open-label design, which was motivated by ethical concerns regarding intramuscular placebo administration, is the risk of investigator bias. For efficacy, there was a notable discordance between INV and BIRC assessments, and for safety, a trend toward underreporting of AEs in the PCET arm emerged in comparison with the expected rates from previous experience, likely related to the wellknown safety profile of comparator ETs.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of endocrine monotherapy as a comparator for second-/third-line treatment in ER+, HER2– aBC, while commonly used, might be argued in some regions where combination therapy is preferred, such as the United States (especially with fit patients). 6 , 32 …”
Section: Discussionmentioning
confidence: 99%